The Effect of Financial Institutions Banking Soundness Against Stock Price - Abu Bakar Akbar (International Journal of Seocology, 2019)
This study was conducted to determine the effect of the soundness of banking financial institutions variable as measured by Return on Assets, Net Interest Margin, and Capital Adequacy Ratio on share prices at government banks in the Indonesia Stock Exchange for the period 2008-2015. The population of this study is the Government commercial banks consisting of BRI Bank, BNI Bank, BTN Bank, and Bank Mandiri. The sample of this study is the assessment of the soundness of government commercial banks on stock prices, with the scope of the assessment covering the factors of ROA, NIM, and CAR. The sample was obtained through the publication of 2008-2015 annual financial statements totaling 32 data. The analysis technique uses multiple linear regression analysis, while the measurement tool uses t test, F test, and the coefficient of determination (R2) test. The results showed that the ROA variable had a positive and significant effect on stock prices, the NIM variable had a negative and significant effect on stock prices, the CAR variable had a positive and significant effect on stock prices at government commercial banks in the Indonesia Stock Exchange.